Pembuatan Soft Cookies dengan Penambahan Puree Mbothe (Xanthosoma sagittifolium L) - Muhammad Al Aziz Putra M; Niken Purwidiani; Sri Handajani; Ita Fatkhur Romadhoni (Journal of Creative Student Research, 2024)
Soft cookies with the addition of mbothe puree are cookies made from flour, eggs, powdered sugar, butter, and mbothe puree. This experiment aims to determine; 1) the results of sensory tests which include shape, color, aroma, taste, and texture; 2) the nutritional value contained, including carbohydrates, fat, protein, fiber and calcium; 3) the selling price of soft cookies with the addition of mbothe puree. This experimental study used a group randomized design with three treatments. From this experiment, researchers can control all external variables that affect the experimental process, data collection is carried out by observation through organoleptic tests including color, shape, aroma, texture, and taste. Data collection was carried out by 30 semi-trained panelists. The data analysis technique used anava, the results showed; 1) there is an effect of adding mbothe puree on taste, aroma and texture and no effect on color; 2) the best product is produced from the addition of 10% mbothe puree and its nutritional content includes 74.15% carbohydrates, 5.67% fat, 13.67% protein, 4.11% fiber and 63.80mg/100g calcium; 3) the selling price of soft cookies with the addition of mbothe puree is Rp. 20,962/100 grams.